The Economic Rate of Return in Small and Household Manufacturing Industries (The Pakistan Development Review, 1988)
Small-scale and Household Manufacturing Industry can contribute to economic development by providing employment; creating jobs with low capital costs: building up a reservoir of skilled and semi-skilled labour; reducing income disparities as small-scale manufacturing is widespread and not concentrated in any specific area or region; developing indigenous technology and raising saving and investment within the country rather than being dependent on external sources. Small-scale manufacturing is also a potential breeding ground for the development of entrepreneurial talent which is of great importance in accelerating the developmental process. In Pakistan, the importance of the small-scale manufacturing industry has not been given its due recognition. The various five-year plans mention small-scale industry but focus their main attention in other areas. For example, to quote from the First Five-Year Plan (1955 - 60):